Physical Activity Patterns of Greek Adults Aged 60 – 90 years: Age and Gender Effects - Michalopoulou, Μαρία; Aggeloussis, Νίκος; Zisi, Βασιλική; Ventouri, Μαρία; Kourtessis, Θωµάς; Malliou, Παρασκευή (Inquiries in Physical Education and Sport, 2006)
Τhe aim of the present study was to evaluate physical activity levels of community-dwelling adults aged over 60 in Greece and find age and gender effects. Physical activity was assessed using the Physical Activity Scale for the Elderly Questionnaire (Washburn et al., 1993) in 486 persons (281 men and 205 women) aged 60–90 yrs (Μ=74.6, SD= 6.82). They were assigned into three age groups: A=61-70, B=71-80, and C= 81-90 years. According to two way analysis of variance, females had significantly higher physical activity total scores when compared to males (p<.01). Men reported a greater participation in activities of moderate intensity (p<.01) and women were significantly more active in physical activities related to household and carrying for others (p<.001). Age effects in physical activity resulted in favor of older adults aged 61-70 years when compared to older adults aged 81-90 years (p<.001). Respective differences were reported for physical activities of moderate intensity (p<.05), for recreational physical activities (p<.01) and for walking (p>.01), although additional differences were reported for walking between older adults aged 71-80 years and 81-90 years. In conclusion, advancing age results to limitation of all forms of physical activities. Sex plays an important role in the type and intensity of physical activities that the elderly are involved.